An atypical IgM class platelet cold agglutinin induces GPVI-dependent aggregation of human platelets - Sánchez Guiu, Isabel M.; Martínez-Martinez, Irene; Martínez, Constantino; Navarro-Fernandez, José; Garcia-Candel, Faustino; Ferrer-Marín, Francisca; Vicente, Vicente; Watson, Steve P.; Andrews, Robert K.; Gardiner, Elizabeth E.; Lozano, María L.; Rivera, José (Thrombosis and Haemostasis, 2015)
Platelet cold agglutinins (PCA) cause pseudothrombocytopenia, spurious thrombocytopenia due to ex vivo platelet clumping, complicating clinical diagnosis, but mechanisms and consequences of PCA are not well defined. Here, we characterised an atypical immunoglobulin (Ig)M PCA in a 37-year-old woman with lifelong bleeding and chronic moderate thrombocytopenia, that induces activation and aggregation of autologous or allogeneic platelets via interaction with platelet glycoprotein (GP)VI. Patient temperature-dependent pseudothrombocytopenia was EDTA-independent, but was prevented by integrin αIIbβ3 blockade. Unstimulated patient platelets revealed elevated levels of bound IgM, increased expression of activation markers (P-selectin and CD63), low GPVI levels and abnormally high thromboxane (TX)A2 production. Patient serum induced temperature- and αIIbβ3-dependent decrease of platelet count in allogeneic donorcitrated platelet-rich plasma (PRP), but not in PRP from Glanzmann’s thrombasthenia or afibrinogenaemia patients. In allogeneic platelets, patient plasma induced shape change, P-selectin and CD63 expression, 14C-serotonin release, and TXA2 production. Activation was not inhibited by aspirin, cangrelor or blocking anti-Fc receptor (FcγRIIA) antibody, but was abrogated by inhibitors of Src and Syk, and by a soluble GPVI-Fc fusion protein. GPVI-deficient platelets were not activated by patient plasma. These data provide the first evidence for an IgM PCA causing platelet activation/aggregation via GPVI. The PCA activity persisted over a five-year follow-up period, supporting a causative role in patient chronic thrombocytopenia and bleeding.
Keywords: Cold agglutinin; human platelet antigens; platelet activation; platelet glycoprotein VI; thrombocytopenia; plasma and platelet lipid composition